Heat Transfer Enhancement of Laminar Nanofluids Flow in a Circular Tube Fitted with Parabolic-Cut Twisted Tape Inserts - Sami D. Salman; Abdul Amir H. Kadhum; Mohd S. Takriff; Abu Bakar Mohamad (The Scientific World Journal)
Numerical investigation has been carried out on heat transfer and friction factor characteristics of copper-water nanofluid flow in a constant heat-fluxed tube with the existence of new configuration of vortex generator using Computational Fluid Dynamics (CFD) simulation. Two types of swirl flow generator: Classical twisted tape (CTT) and Parabolic-cut twisted tape (PCT) with a different twist ratio (y = 2.93, 3.91 and 4.89) and different cut depth (w = 0.5, 1.0 and 1.5 cm) with 2% and 4% volume concentration of CuO nanofluid were used for simulation. The effect of different parameters such as flow Reynolds number, twist ratio, cut depth and nanofluid were considered. The results show that the enhancement of heat transfer rate and the friction factor induced by the Classical (CTT) and Parabolic-cut (PCT) inserts increases with twist ratio and cut depth decreases. The results also revealed that the heat transfer enhancement increases with an increase in the volume fraction of the CuO nanoparticle. Furthermore, the twisted tape with twist ratio (y = 2.93) and cut depth w = 0.5 cm offered 10% enhancement of the average Nusselt number with significant increases in friction factor than those of Classical twisted tape.